Potential Relevance of Bioactive Peptides in Sports Nutrition - Daniel König (MDPI AG, 2021)
Bioactive peptides are physiologically active peptides mostly derived from proteins following gastrointestinal digestion, fermentation or hydrolysis by proteolytic enzymes. It has been shown that bioactive peptides can be resorbed in their intact form and have repeatedly been shown to have a positive effect on health-related parameters such as hypertension, dyslipoproteinemia, inflammation and oxidative stress. In recent years, there has been increasing evidence that biologically active peptides could also play an important role in sports nutrition. Current studies have shown that bioactive peptides could have a positive impact on changes in body composition and muscular performance, reduce muscle damage following exercise and induce beneficial adaptions within the connective tissue. In the following overview, potential mechanisms as well as possible limitations regarding the sports-related effect of bioactive peptides and their potential mechanisms are presented and discussed. In addition, practical applications will be discussed on how bioactive peptides can be integrated into a nutritional approach in sports to enhance athletic performance as well as prevent injuries and improve the rehabilitation process.